Three-dimensional launch simulation and active cooling analysis of a single-shot electromagnetic railgun. (December 2014) - Zhao, Han; Souza, Jeferson A; Ordonez, Juan C
An electromagnetic railgun is one of the applications of electromagnetic launchers, which are devices used to accelerate projectiles to velocities exceeding those attained with conventional propelling systems. A magnetic field is generated when current flows through two conductive rails connected by a moving armature. The current that passes through the rails exerts an electromagnetic force on the armature and causes it to accelerate to high speeds. In this work, a three-dimensional transient model for the thermal and electromagnetic solutions of the launch process is presented. The model accounts for the determination of the current and temperature profiles inside the rails, the projectile movement, and the cooling process after the first launch. Focus is given to the thermal management where five different arrangements, one without cooling and four that include cooling channels, are studied. A 10 to 50 K reduction in the peak temperature was obtained with the inclusion of cooling channels when compared to the no-cooling-channel case. It was also shown that the position and size of these channels can be optimized in order to reduce this peak temperature.